Female Firefighter Work-Related Injuries in the United States and Canada: An Overview of Survey Responses - Pawer, Samantha; Turcotte, Kate; Desapriya, Ediriweera; Zheng, Alex; Purewal, Amanat; Wellar, Alyssa; Kunz, Kenneth; Garis, Len; Thomas, Larry S.; Pike, Ian (Frontiers in Public Health, 2022)
Objectives: This study explored how demographic characteristics, life experiences, and firefighting experiences have an impact on work-related injuries among female firefighters, and described events surrounding such work-related injuries. Methods: This online survey was available from June 2019 to July 2020. Questions related to demographic characteristics, life experiences, firefighting experiences, and work-related injuries. The final sample included 1,160 active female firefighters from the US and Canada. Descriptive analyses characterized variables by the presence or absence of work-related injury, injury severity, job assignment, and country of residence. Results: There were 742 female firefighters (64%) that reported having at least one work-related injury. US respondents made up 67% of the sample, but 75% of those who reported an injury. The proportion of US respondents increased with increasing injury severity. Injured respondents had been in the fire service longer and had a greater number of fires and toxic exposures than non-injured respondents. Heavier weight, tobacco use, and alcohol consumption were more common among injured respondents. The two most common contributing factors to work-related injuries were human error and firefighter fatigue. Among respondents who reported an injury-related time loss claim, 69% were wearing protective equipment when injured, and 9% of the injuries directly resulted in new policy implementation. Conclusions: These findings can help inform resource allocation, and development of new policies and safety protocols, to reduce the number of work-related injuries among female firefighters.